2019
DOI: 10.1007/s00217-019-03390-1
|View full text |Cite
|
Sign up to set email alerts
|

Functional fungal extracts from the Quorn fermentation co-product as novel partial egg white replacers

Abstract: The production of mycoprotein biomass by Marlow Foods for use in their meat alternative brand Quorn is a potential source of sustainable alternatives to functional ingredients of animal origin for the food industry. The conversion of this viscoelastic biomass into the Quorn meat-like texture relies on functional synergy with egg white (EW), effectively forming a fibre gel composite. In a previous study, we reported that an extract (retentate 100 or R100) obtained from the Quorn fermentation co-product (centrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…The increased viscosity of mycoprotein solution is caused by mycelial fragments and viscosifying substances, including galactan, chitin, and chitosan, which inhibit the flow of fermenting broth. Similarly, Lonchamp et al (2020a) studied the impact of mycoprotein and mycoproteinbased fractions (retentates) on the viscosity and gelling properties of egg white (EW) solutions with different concentrations (50/50 and 75/25 EW/retentate). The study found that the retentate and EW/retentate solutions exhibited higher viscosity (0.9, 0.12, and 0.08 Pas) than 10% EW (0.02 Pas).…”
Section: Rheological Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The increased viscosity of mycoprotein solution is caused by mycelial fragments and viscosifying substances, including galactan, chitin, and chitosan, which inhibit the flow of fermenting broth. Similarly, Lonchamp et al (2020a) studied the impact of mycoprotein and mycoproteinbased fractions (retentates) on the viscosity and gelling properties of egg white (EW) solutions with different concentrations (50/50 and 75/25 EW/retentate). The study found that the retentate and EW/retentate solutions exhibited higher viscosity (0.9, 0.12, and 0.08 Pas) than 10% EW (0.02 Pas).…”
Section: Rheological Propertiesmentioning
confidence: 99%
“…Finnigan et al (2017) found that Quorn products need functional synergy with EW to achieve a meat-like texture. Moreover, Lonchamp et al (2020a) examined the interaction between mycoprotein retentate mixture and EW and discovered that gels produced from a 25/75 and 50/50 ratio of retentate mixture and EW exhibited similar foaming properties to 10% EW but greater than 5% and 7.5% EW. The study found that gels made from a mixture of EW-retentate (75/25) exhibited a dense hyphal structure that encloses the filaments and other particles surrounding the air bubbles.…”
Section: Meat-like Texturementioning
confidence: 99%
See 1 more Smart Citation
“…Myco in baseline con guration), while this option could be contemplated (Lonchamp et al, 2020). This modeling choice goes in hand with the low information on water integration of future IL-based lignocellulosic biore neries, and that many parameters sizing the actual amount of water required might signi cantly evolve (e.g.…”
Section: Mycoproteins Production From Residual-based Sugars: Forecast...mentioning
confidence: 99%
“…Algal proteins can be obtained from a relatively sustainable source, since algae i) is a rich source of proteins; ii) do not compete with traditional food crops for land; iii) is a multiuse crop (fuel, food, feed..); and iv) mitigate greenhouse gas emissions (Tredici et al 2015;Klamczynska and Mooney 2017;Laurens et al 2017). Fungal proteins do not require agricultural land and may be obtained through a circular economy based on recycling agri-industrial wastes (Ritala et al 2017;Satari and Karimi 2018;J. Lonchamp et al 2019;Finnigan, Needham, and Abbott 2016).…”
Section: Trends In the Market Of Animal-free Proteinsmentioning
confidence: 99%